2014
DOI: 10.5901/mjss.2014.v5n6p53
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organisational Employee Engagement Strategies on Organisational Citizenship Behaviour within Retail Banking. A Case of Amatole District Municipality

Abstract: This study aims to investigate the influence of employee engagement strategies on organisational citizenship behaviour within the retailing banking industry. A survey design was used to realise the research objectives. The sample population was 180 employees of the retail banking sector in Amatole District. A self-designed questionnaire on employee engagement was used as a measuring instrument together with Gallup's workplace audit questionnaire and Organisational Citizenship Behaviour Measure designed by Pods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…relationship between EE and OCB, was also accepted. This finding is in line with the previous studies exploring the relationship between EE and OCB (Banhwa et al, 2014;Latha and Deepa, 2017;Safitri et al, 2017;Saks, 2019). Notably, the finding is contrary to the claim made by Newton and LePine (2018) who argue that in organizations with monotonous work, disengaged employees are more likely to exhibit citizenship behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…relationship between EE and OCB, was also accepted. This finding is in line with the previous studies exploring the relationship between EE and OCB (Banhwa et al, 2014;Latha and Deepa, 2017;Safitri et al, 2017;Saks, 2019). Notably, the finding is contrary to the claim made by Newton and LePine (2018) who argue that in organizations with monotonous work, disengaged employees are more likely to exhibit citizenship behavior.…”
Section: Discussionsupporting
confidence: 90%
“…such employees exhibit OCB. Based on the studies (Avey et al, 2008;Babcock-Roberson and Strickland, 2010;Anand and Banu, 2011;Ram and Prabhakar, 2011;Ahmed et al, 2012;Shantz et al, 2013;Ariani, 2013Ariani, , 2014Banhwa et al, 2014;Latha and Deepa, 2017;Safitri et al, 2017;Saks, 2019), it is inferred that highly engaged employees are more likely to be involved in exhibiting discretionary behavior at the workplace. Shafiee et al (2020) are of the view that engagement influences citizenship behavior through relationship quality.…”
Section: Conceptual Framework and Hypotheses Development Employer Brand Experience And Organizational Citizenship Behaviormentioning
confidence: 99%
“…A study of the relationships among supportive leadership, engagement, and OCB in service organizations found that followers’ perception of their leaders and the meaningfulness of their work affected the extent to which they engaged in OCB (Ariani, ). Banhwa, Chipunza, and Chamisa () also found that employees’ engagement on their job leads to increased OCB in the service industry.…”
Section: The Aspects Of Empowermentmentioning
confidence: 93%
“…Guided by the norms of reciprocity, employees manifest different aspects of OCB in response to the treatment they receive (Banhwa et al, ). In this study, those who perceived that they were being treated unfairly were less likely to engage in OCB.…”
Section: Fostering Ocbmentioning
confidence: 99%
“…Based on the pre-survey research result, it was found that some employees still did not show the OCB behavior, including not being willing to help coworkers who were having difficulty doing their jobs, not doing work outside of their job descriptions, not cooperating with fellow colleagues, there were still conflicts between fellow employees and superiors and less actively participate in the activities held by the company. Some research results, including Banhwa et al (2014), found that OCB was influenced by Organizational Employees and Engagement Strategies. According to Zanuchi et al (2014) and Badawy et al, (2016), OCB is influenced by organizational culture and job satisfaction.…”
Section: Introductionmentioning
confidence: 99%